Analysis of the composite variance of dissected splitting experiments carried out according to the Latin box design - المشهداني, كمال علوان; عبد الحسين, كاظم يحيى (Journal of Economics and Administrative Sciences, 2011)
In this research we present An idea of setting up same split plots experiments in many locations and many periods by Latin Square Design. This cases represents a modest contribution in area of design and analysis of experiments. we had written (theoretically)  the general plans, the mathematical models for these experiments, and finding the derivations of EMS for each component (source) of sources of variation of the analysis of variance tables which uses for the statistical analysis for these expirements